Subclinical Infections of Anaplasma phagocytophilum and Anaplasma bovis in Dogs from Ibaraki, Japan - Fukui, Yuichi; Inokuma, Hisashi (Japanese Journal of Infectious Diseases, 2019)
We evaluated the prevalence of Anaplasma infection in 332 dogs from Ibaraki, Japan, using serological and molecular methods. An immunofluorescence antibody assay against Anaplasma phagocytophilum indicated that 7 of the 328 serum samples tested (2.1%) were positive for A. phagocytophilum. Screening by polymerase chain reaction (PCR) analysis demonstrated that 8 of the 331 peripheral blood samples tested (2.4%) were positive for Anaplasmataceae. Phylogenetic analysis of the partial 16S rRNA sequence of the PCR amplicons revealed that 6 sequences were most similar to the 16S rRNA sequence of a Wolbachia sp., and the remaining 2 to A. bovis. Further analysis by A. phagocytophilum-specific nested PCR demonstrated that 1 dog infected with A. bovis was also positive for A. phagocytophilum. This is the first study to report the dual infection of a dog in Japan with A. bovis and A. phagocytophilum.